Temporal trends in Finnish agricultural soils: A comparative analysis of national and LUCAS soil monitoring datasets - Heikkinen, Jaakko; Kostensalo, Joel; Keskinen, Riikka; Soinne, Helena; Nuutinen, Visa (Wiley-Blackwell, 2024)
Finnish agricultural soil conditions are regularly monitored both through national and European Union (EU)-wide LUCAS Soil sampling. In this study, we compare temporal trends and variability in organic carbon content (OC), pH, phosphorus (P) and potassium (K) in 2009–2018 across the two datasets. The national monitoring programme encompasses more monitoring plots (620 vs. 134 in 2018), while LUCAS sampling is repeated more frequently and in addition to 2009 and 2018, it also includes data from 2015. The temporal variability in all examined indicators was substantially higher in the LUCAS dataset compared to the national monitoring data. In mineral soils, Spearman's rank correlation coefficient between element contents measured in 2009 and 2018 ranged between 0.82 and 0.94 in the national dataset, and between 0.52 and 0.67 in the LUCAS dataset. The results for organic soils mirrored those of mineral soils. The higher variability in the LUCAS dataset may be attributed to less precise geolocation of sampling plots and/or variations in the sampling protocol such as greater sampling depth and the use of a spade instead of a core auger. The greater temporal variability, coupled with a smaller number of sampling plots in the LUCAS dataset, resulted in lower statistical power making the detection of trends with a realistic magnitude more challenging. Further, in LUCAS data, the confidence intervals of trends were of the same magnitude, regardless of whether the data from the year 2015 was included or not. The national dataset was found to be sufficient for detecting nationwide trends in element contents. Our results indicate that refining sampling protocols and improving the location accuracy of sampling plots are more cost-effective approaches to enhance the precision of temporal trend estimation than increasing the number of sampling plots.
Keywords: Finland; agricultural soils; temporal trends; organic carbon; phosphorus; potassium